Tomato Growth and Production under Different Concentrations of Weed Extract-Based Biostimulant in Dry Season - Rohman, Fadil; Firgiyanto, Refa; Dinata, Gallyndra Fatkhu; Rohman, Hanif Fatur; Siswadi, Edi; Sukri, M. Zayin; Fadilah, Anggita Rizqy; Firdausi, Haikal (P3M Politeknik Negeri Jember, 2025)
Tomato farmers in Indonesia face challenges such as unpredictable weather conditions that can affect crop yields. Climatic stress, such as drought and heat, can have significant effects on plant growth. Plant Biostimulant have been shown to alleviate climatic stress in plants by modifying physiological processes and enhancing stress tolerance, ultimately improving crop growth and productivity. Recently, weed extract can serve as a biostimulant to improve growth and productivity of crops. This research aimed to determine the best concentration of weed extract-based biostimulant (WEBB) to increase tomato growth and production in dry season. The research was conducted on June to September 2024 in Tutul Village, Balung District, Jember Regency. The research used Randomized Block Design consisted of five levels of WEBB concentrations, i.e. 0, 1, 2, 3 and 4 ppm. The concentration of WEBB at 1 ppm significantly increased early growth of stem and the number of leaves at 2 WAP by 16.39% and 39.02% respectively. The application of WEBB at 1–2 ppm also showed a significant increase in the number of fruits by 24.49% compared to control. This indicated that 1 ppm WEBB were effective in stimulating the early growth and fruit formation on tomato plant.